Criminology in Action: Examining Corruption in Russia Under the Lens of Criminological Theories - Choi, Jean (2013)
The purpose of this research paper is to investigate whether there exist alterative methods ofexamining the widespread nature of corruption in Russia. According to Transparency International’s most recently published Corruption Perceptions Index 2012, Russia ranks 133 out of 176 countries and territories, indicating that Russia’s public sector is perceived to be a corrupt as those of the Comoros, Guyana, Honduras, Iran, and Kazakhstan. This paper advocates the view that what is currently needed most is not solutions or prescriptive measures to curb such high levels of reported corruption in Russia. Rather, this paper seeks to ultimately gain a better understanding of the conditions behind Russia’s consistently low-ranking with regards to its high levels of perceived corruption. To achieve this aim, a method of examining corruption under the lens of criminological theories is proposed. Corruption is defined as the acceptance of bribes in Russia’s civil service system. Based on a review of relevant criminological theories and an examination of the supporting body of academic literature, criminological theories deemed most applicable to the study of corruption in Russia’s civil service system are rational choice theory, social control theory, and strain theory. In contrast, theories requiring further research before any direct applications can be established include critical theory, biological theory, and labeling theory. The paper ends by highlighting several areas that deserve further study in order to advance with this newly proposed method of examining corruption in Russia